2017
DOI: 10.1590/1678-457x.20416
|View full text |Cite
|
Sign up to set email alerts
|

Screening of traditional South African leafy vegetables for specific anti-nutritional factors before and after processing

Abstract: This study investigated the effect of processing on anti-nutritional factors of thirteen traditional leafy vegetables collected in Kwa Zulu-Natal, South Africa. The aim was to determine whether processing reduced anti-nutrient levels of leafy vegetables. The vegetables were boiled in a plant-to-distilled water ratio of 1:4 (w/v) at 97 °C for a time period of 5 and 15 min. The vegetables studied were: Amaranthus dubius, Amaranthus hybridus, Asystasia gangetica, Bidens pilosa, Ceratotheca triloba, Chenopodium al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 21 publications
(37 reference statements)
3
43
0
2
Order By: Relevance
“…A study by Virginia et al (2012) on effects of cooking and processing on oxalate content in green leafy vegetables and pulses revealed that blanching, pressure cooking for 10 min and open pan cooking of green leafy vegetables reduced their oxalate concentration from 88.8 mg/100 g fresh samples to 48.4, 57.2 and 60.13 mg/100 g, respectively. Other studies reported reduction of oxalates in boiling and drying of vegetables (Essack et al, 2017;Ilelaboye et al, 2013;Mwanri et al, 2011); which means the amount of oxalate present in studied vegetables may not be harmful for human consumption since the contents were relatively low and these vegetables are usually boiled before consumption.…”
Section: Discussionmentioning
confidence: 84%
“…A study by Virginia et al (2012) on effects of cooking and processing on oxalate content in green leafy vegetables and pulses revealed that blanching, pressure cooking for 10 min and open pan cooking of green leafy vegetables reduced their oxalate concentration from 88.8 mg/100 g fresh samples to 48.4, 57.2 and 60.13 mg/100 g, respectively. Other studies reported reduction of oxalates in boiling and drying of vegetables (Essack et al, 2017;Ilelaboye et al, 2013;Mwanri et al, 2011); which means the amount of oxalate present in studied vegetables may not be harmful for human consumption since the contents were relatively low and these vegetables are usually boiled before consumption.…”
Section: Discussionmentioning
confidence: 84%
“…Food processing may affect the functionality and nutritional quality of the food products [34]. Also, it leads to beneficial transformations, compound degradation, or nutrient loss [35]. The effect of boiling on proximate composition of Solanum nigrum leaves is given in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Leunca termasuk sedikit di antara anggota Solanaceae yang dimanfaatkan bagian daun dan buah sekaligus dan yang lebih banyak dikonsumsi adalah buah atau umbinya seperti cabe, terong, tomat, dan kentang. Daun atau pucuk S. nigrum mengandung glikosida atau nitrat dalam jumlah tinggi (Masinde et al 2007;Essack et al 2017). Sudah diketahui bahwa kandungan glikosida dan nitrat dipengaruhi oleh nitrogen (Bvenura & Afolayan 2014;Putriantari & Santosa 2014;Janet et al 2016;Ou et al 2017;Sabu & Kalpana 2017).…”
Section: Pendahuluanunclassified